Methodological Approaches to Preclinical Evaluation of General Toxicity of Therapeutic Radiopharmaceuticals - O. E. Klementyeva; A. S. Lunev; C. A. Lunyova (Регуляторные исследования и экспертиза лекарственных средств, 2021)
Radiopharmaceuticals differ from other medicines mainly by the specific nature of their pharmacological action based on radioactivity, by absence of multiple-dose regimens, and by miniscule concentrations of the active pharmaceutical ingredient (10-9–10-12 mol/L). However, the official regulations and standards do not contain specific requirements for preclinical evaluation of radiopharmaceuticals. The aim of the study was to summarise preclinical data on general toxicity of therapeutic radiopharmaceuticals, which were obtained by the Laboratory of Preclinical and Clinical Studies of Radiopharmaceuticals of the Federal State Budgetary Institution ‘State Research Center of the Russian Federation¾Burnasyan Federal Medical Biophysical Center’ of the Federal Medical Biological Agency. Results: the authors analysed criteria for: selection of the study design based on physico-chemical nature of the active pharmaceutical ingredient; calculation of doses and selection of dosage regimens for radiopharmaceuticals with different administration routes; radiation safety for personnel performing the study. The authors used the data on three therapeutic radiopharmaceuticals to formulate methodological approaches to preclinical evaluation of their general toxic properties. The analysis of long-term experience in preclinical studies of therapeutic radiopharmaceuticals demonstrated the need for a judicious individual approach to the development of a preclinical study design. The authors proposed methodological approaches to preclinical evaluation of general toxic properties of therapeutic radiopharmaceuticals, which make it possible to adequately assess potential toxic effects and obtain meaningful study results. Conclusions: there is a need for a specific guideline for preclinical studies of therapeutic radiopharmaceuticals, which would take into account specific pharmacological action and nuclear-physical characteristics of radionuclides.